Analisis Komparatif Metode FFT Dan Least Squares Dalam Penentuan Komponen Pasang Surut Di Perairan Indonesia - Al-Ghifari, Najwan; Budiarsa, Anugrah Aditya; Ritonga, Irwan Ramadhan; Riza, Muhammad; Sihotang, Zetsaona; Mandang, Idris (Jurnal Laut Khatulistiwa, 2026)
This study evaluates the performance of Fast Fourier Transform (FFT) and Least Squares (LS) methods in tidal analysis across four strategic locations representing Indonesia's diverse tidal regimes: Belitung, Bontang, Melonguane, and Natuna. Eight principal tidal components (O1, K1, M2, S2, N2, K2, P1, Q1) were analyzed. The results demonstrate that the Least Squares method is significantly superior, achieving an RMSE reduction of 79.2% to 94.0% compared to FFT. While tidal classifications based on Formzahl numbers remained consistent across both methods—identifying diurnal types in Belitung and mixed-prevailing semidiurnal types elsewhere—the LS method provided more precise harmonic constants. These findings recommend the LS method for high-accuracy operational tidal modeling and sea-level prediction in Indonesian waters.